The poisoned city : Flint's water and the American urban tragedy - Clark, Anna (Anna Leigh) (Metropolitan Books, Henry Holt and Company, 2018)
"Recounts the gripping story of Flint's poisoned water through the people who caused it, suffered from it, and exposed it. It is a chronicle of one town, but could also be about any American city, all made precarious by the neglect of infrastructure"--